Human Resource Management Practices : Assessing Added Value - Andresen, Maike; Nowak, Christian (Management for Professionals, 2015)
This book is designed to help practitioners and academics to assess the added value of HR practices. It provides hands-on recommendations for choosing effective means to manage HR and specific suggestions aimed at facilitating the measurement of HR practices' impact on value creation. Evidence-based recommendations are made by drawing on thorough empirical research from various research traditions and academic disciplines. It covers a wide variety of tasks faced by the HR function and specifically addresses new challenges such as assessing the added value of work-life balance practices.